2008
DOI: 10.1080/09513590802288218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hand functions in women with polycystic ovary syndrome

Abstract: Japanese women now account for 43 percent of the labor force. A number of them are involved in construction, agricultural and forestry jobs. The aim of this study was to establish a non-invasive technique for the evaluation of peripheral circulatory functions in women with Raynaud's phenomenon (RP) and introduce a specific method for the assessment of vascular disturbances in females exposed to hand-transmitted vibration. The subjects of this study were 10 women with primary RP, 7 women with progressive system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
14
1
2
Order By: Relevance
“…Another study, using a Jamar dynamometer to evaluate the isometric handgrip strength of the dominant limb, found no difference in muscle strength between women with PCOS and age-matched healthy women. However, the limitation of that study was the lack of information about parameters that may affect muscular strength such as IR [21]. These findings differ from ours results showing higher isometric handgrip strength levels of the same muscle groups in women with PCOS than in control women.…”
Section: Discussioncontrasting
confidence: 90%
“…Another study, using a Jamar dynamometer to evaluate the isometric handgrip strength of the dominant limb, found no difference in muscle strength between women with PCOS and age-matched healthy women. However, the limitation of that study was the lack of information about parameters that may affect muscular strength such as IR [21]. These findings differ from ours results showing higher isometric handgrip strength levels of the same muscle groups in women with PCOS than in control women.…”
Section: Discussioncontrasting
confidence: 90%
“…There was no difference in marital status, employment status, and parity between the two groups in three studies (5,12,13), and these parameters were not reported in the other study (10). Of the five studies that reported mean anxiety scores, three had significantly higher anxiety scores in PCOS women compared with control women (Table 2) (11,14,15). In all three studies there was no significant difference in age and BMI between the two groups.…”
Section: Resultsmentioning
confidence: 90%
“…One study included age-and BMI-matched subjects and reported a higher prevalence of generalized anxiety and phobias in women with PCOS (12). In four other studies with no significant difference in BMI between PCOS and control subjects, the anxiety scores were significantly higher in three (11,14,15). Another potential factor that may contribute to anxiety symptoms in women with PCOS is an unfulfilled wish to conceive.…”
Section: Discussionmentioning
confidence: 98%
“…In five studies, BMI was either matched between groups 21,22 or not significantly different. 20,26,30 Figure 4 shows the subanalysis of these studies, and the risk of abnormal depression scores remained significantly increased in women with PCOS (OR 4.09, 95% CI 2.62-6.41). The heterogeneity between these studies was not significantly different (Fig.…”
Section: Dokras Depression In Women With Pcos Obstet Gynecol 2011mentioning
confidence: 99%